The value of water in Bolivia: An economic resource or a human right? - Enrique Casta\~nón Ballivián (Institute for Advanced Development Studies (INESAD), 2010)
After the 2000 Water-War, access to water in Bolivia has become a major social demand and thus a prime and contentious political issue. The event has revealed an overwhelming opposition to neo-liberal approaches to water management and has allowed the articulation of a new discourse that sees water not as an economic resource but as a human right. In this context, the paper reviews the two contrasting positions within the debate about whether or not water should be treated as an economic resource. In doing so, it presents the arguments underpinning each position which then allows the elaboration of some relevant conclusions.
Keywords: Q20; Q25; 330; Value of water; Bolivia; economic resource; water-war; market value; indigenous knowledge; cultural value; Ressourcenökonomik; Erneuerbare Ressourcen; Wasser; Bolivien